Comparative Review on Feature-content Based of Public Key Steganography Trends - Hafizah Abdul-Razak, Nor; Din, Roshidi; Ahmad, Mazida (International Journal of Engineering and Technology, 2018)
Â This paper intends to provide an up-to-date review on studies conducted in the field of Public Key Steganography (PKS). It is based on feature-content of PKS which are domain, scheme, and evaluation parameter aspects. It is concentrate on type of domain in PKS; schemes applied in PKS, and commonly used evaluation parameters in evaluating the performance of PKS system. Findings of this study are grouped into several subsections based on type of domain, schemes, and evaluation parameters. This review provides brief information related to important component in PKS environments. It provides an added value to the knowledge of PKS and also as a source of information to other researchers in conducting their study in the field of PKS. Besides, this study also provides a recommendation and good practices drawn from the reviewed literatures.Â Â